Callus Induction of Marigold Plants (Tagetes Erecta L) with a Combination of 2,4D and Kinetin - Suwinda Fibriani (CERED Indonesia Institute, 2023)
Marigold flower (Tagetes erecta L.) is an ornamental flowering plant that belongs to the Astarecae family. Marigold flowers are used as ornamental plants in pots and as flower bouquets. The demand for marigold flowers is very high, so efforts are needed to quickly propagate marigold plants and produce good quality. Efforts to provide marigolds are carried out by increasing the production and quality of marigold plants. Tissue culture is an in vitro technique of plant propagation and is effective in producing large, uniform and disease-free plants. Giving ZPT 2,4-D and Kinetin can stimulate good callus growth and affect the success of callus induction. This study aims to determine the effect of giving 2,4-D and kinetin on the growth of marigold callus induction. The experiment used a randomized block design consisting of two factors, namely 2, 4-D with four concentration levels, namely 0 ppm, 0.5 ppm, 1 ppm and 2 ppm and kinetin with four concentration levels, namely 0 ppm, 0.5 ppm, 1 ppm and 2 ppm with three replicates. The results showed that the combination treatment without 2,4-D and 0.5 ppm kinetin gave the best response when callus appeared 11.67 HST and the treatment of 1 ppm 2,4-D and 2 ppm kinetin gave the best response on the percentage of successful callus induction marigolds.